Tecovirimat in the management of poxviruses: a narrative review of available evidence - Olalekan John Okesanya; Jerico Bautista Ogaya; Ikponmwosa Jude Ogieuhi; Mohamed Mustaf Ahmed; Bonaventure Michael Ukoaka; Ojoisimi Franca Jamgbadi; Deborah Oluwaseun Shomuyiwa; Don Lucero-Prisno Eliseo; Blessing Olawunmi Amisu; Olakulehin Adebusuyi; William K. Chung; Emery Manirambona; et al. (The Egyptian Journal of Internal Medicine)
Abstract Introduction Tecovirimat (TPOXX) is an effective antiviral medication recommended for treating smallpox and other Orthopoxvirus infections. With the rise in monkeypox (mpox) cases globally, there is an urgent need to explore therapeutic options to manage potential outbreaks. Methodology A literature search was conducted using keywords from Scopus and ClinicalTrials.gov. English studies from 2018 to 2024 were included. Results Ten studies assessing the effectiveness and safety of tecovirimat for poxvirus infections were evaluated, reporting diverse findings across different patient populations and study designs. Clinical trials have shown significant therapeutic potential. Various doses of tecovirimat were used in rabbit and mpox models. Early intervention slowed disease progression in vulnerable populations, such as people living with HIV (PLWHIV). Recovery times, virus eradication, and symptom relief varied among studies, but wider access and usage showed better clinical symptoms and tolerable side effects. Tecovirimat’s efficacy against circulating strains has been experimentally demonstrated. Conclusion Tecovirimat shows promise for treating poxvirus infections. Clinical trials are expected to provide more evidence-based findings to inform future therapeutic approaches and public health campaigns. Future research should explore tecovirimat’s potential in managing emerging poxvirus outbreaks, such as borealpox and mpox, to strengthen and promote public health.